Aryl hydrocarbon receptor deletion in cerebellar granule neuron precursors impairs neurogenesis. Issue 5 (May 2016) - Dever, Daniel P.; Adham, Zachariah O.; Thompson, Bryan; Genestine, Matthieu; Cherry, Jonathan; Olschowka, John A.; DiCicco‐Bloom, Emanuel; Opanashuk, Lisa A.
Abstract : The cover image, by Daniel P. Dever et al., is based on the Research Article Aryl Hydrocarbon Receptor (AhR) Deletion in Cerebellar Granule Neuron Precursors Impairs Neurogenesis, DOI:10.1002/dneu.22330 .